Screening of heat stress-regulating active fractions in mung beans - Feng, Yuchao; Fan, Xia; Suo, Dengcheng; Zhang, Shu; Ma, Yantao; Wang, Haoyu; Guan, Xin; Yang, Hongzhi; Wang, Changyuan (Frontiers in Nutrition, 2023)
Introduction Heat stress caused by high temperatures has important adverse effects on the safety and health status of humans and animals, and dietary interventions to alleviate heat stress in daily life are highly feasible. Methods In this study, the components of mung bean that have heat stress-regulating effects were characterized by in vitro antioxidant indicators and heat stress cell models. Results As a result, 15 target monomeric polyphenol fractions were identified based on untargeted analysis on an ultra performance liquid chromatography coupled with high field quadrupole orbit high resolution mass spectrometry (UHPLC-QE-HF-HRMS) platform and available reports. The results of DPPH and ABTS radical scavenging showed that mung bean polyphenols (crude extract) and 15 monomeric polyphenols had better antioxidant activity, followed by oil and mung bean peptides, while protein and polysaccharides had relatively poor antioxidant activity. Qualitative and quantitative assays for 20 polyphenols (15 polyphenols and 5 isomers) were then established based on platform targets. Vitexin, orientin, and caffeic acid were identified as monomeric polyphenols for heat stress control in mung beans based on their content. Finally, mild (39°C), moderate (41°C), and severe (43°C) heat stress models were successfully constructed based on mouse intestinal epithelial Mode-k cells and human colorectal adenocarcinoma Caco-2 cell lines, all with an optimal heat stress modeling time of 6 h. Screening of mung bean fractions using HSP70 mRNA content, a key indicator of heat stress. As a result, HSP70 mRNA content was significantly up-regulated by different levels of heat stress in both cell models. The addition of mung bean polyphenols (crude extract), vitexin, orientin, and caffeic acid resulted in significant down-regulation of HSP70 mRNA content, and the higher the level of heat stress, the more significant the regulation effect, with orientin having the best effect. Mung bean proteins, peptides, polysaccharides, oils and mung bean soup resulted in increased or no change in HSP70 mRNA levels after most heat stresses. Discussion The polyphenols were shown to be the main heat stress regulating components in mung bean. The results of the validation experiments confirm that the above three monomeric polyphenols may be the main heat stress regulating substances in mung bean. The role of polyphenols in the regulation of heat stress is closely linked to their antioxidant properties.